THE STUDY OF SEWING TERMINOLOGY IN LINGUISTICS - Mirzayeva Gulasal Ergashovna; Bo’ronova Mekkamtosh Xoliqulovna (Western European Studies, 2025)
This article analyzes the study of terms related to the field of craftsmanship (tailoring) in Uzbek linguistics, their lexical and semantic characteristics, their place as a linguistic wealth formed through folk oral art and historical sources. During the study, the differences between terms and professional lexicon, their connection with the life and cultural development of the people were highlighted. Also, examples of ancient professional lexicon in the Uzbek language were considered on the example of clothing and tailoring terms found in the works of Alisher Navoi.
Keywords: linguistics; term; professional lexicon